2017
DOI: 10.1021/acsami.7b11916
|View full text |Cite
|
Sign up to set email alerts
|

Design of Porous/Hollow Structured Ceria by Partial Thermal Decomposition of Ce-MOF and Selective Etching

Abstract: Metal-organic frameworks (MOFs) have been widely used to prepare corresponding porous metal oxides via thermal treatment. However, high temperature treatment always leads to obtained metal oxides with a large crystallite size, thus decreasing their specific surface area. Different from the conventional complete thermal decomposition of MOFs, herein, using Ce-MOF as a demonstration, we choose partial thermal decomposition of MOF, followed by selective etching to prepare porous/hollow structured ceria because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 36 publications
(50 reference statements)
3
32
0
2
Order By: Relevance
“…The bond length of CeÀOi si nt he range from 2.381(2) to 2.735(2) ,w hich is roughlyc onsistentw ith other Ce-based MOFs. [27][28][29] Li + is linked by four oxygen atoms from four carboxylate groups of four different pmal igands ( Figure 1c)w ith bond lengths in the range of 1.929(7)-2.015(6) ( Table 2), which is consistent with the LiÀOb ond length in other compounds. [30] The more interesting phenomenon is that the nearest CeÀLi distance is about 3.559(6)-3.578(6) ,w hich suggests that some interaction exists between adjacent Ce and Li atoms.…”
Section: Structural Descriptionsupporting
confidence: 78%
“…The bond length of CeÀOi si nt he range from 2.381(2) to 2.735(2) ,w hich is roughlyc onsistentw ith other Ce-based MOFs. [27][28][29] Li + is linked by four oxygen atoms from four carboxylate groups of four different pmal igands ( Figure 1c)w ith bond lengths in the range of 1.929(7)-2.015(6) ( Table 2), which is consistent with the LiÀOb ond length in other compounds. [30] The more interesting phenomenon is that the nearest CeÀLi distance is about 3.559(6)-3.578(6) ,w hich suggests that some interaction exists between adjacent Ce and Li atoms.…”
Section: Structural Descriptionsupporting
confidence: 78%
“…The textural properties were calculated based on the N 2 adsorption/desorption measurements, as listed in Table 1. It was shown that before pyrolysis, Ce-MOF-808 and Ce-UiO-66 exhibited large specific surface areas of 469.4 and 425.0 m 2 /g, respectively, while Ce-BTC possessed a specific surface area of 28.9 m 2 /g with small micropores [26]. The specific surface area values of Ce-MOF-808 and Ce-UiO-66 were lower than those previously reported [23,25].…”
Section: Structural Analysis Of Ce-mofsmentioning
confidence: 71%
“…The specific surface areas of MOF-808 and UiO-66 decreased greatly to 96.6 and 38.8 m 2 /g, respectively, while that of Ce-BTC increased to 71.5 m 2 /g. The increase of the Ce-BTC surface area was due to the formation of a porous structure after calcination [26].…”
Section: Structural Analysis Of Ceo 2 -Mofsmentioning
confidence: 99%
“…Artificial templating agents/precursors can be based on pure organics and polymers [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], silicon-organic compounds and mesoporous silica [ 27 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ], metal-organic frameworks [ 42 , 43 ], synthetic carbon materials [ 44 , 45 , 46 , 47 ], etc.…”
Section: General Strategies For Template Synthesis Of Porous Catalmentioning
confidence: 99%